Fortalecimiento a las asociaciones de artesanos que elaborandulces tradicionales en la parroquia Timbara del cantón Zamora en el ámbito turístico - Juela Torres, Edita Nathali (2016)
The development of peoples depends on the good management of their resources. The "A STRENGTHENING PARTNERSHIPS WHICH PRODUCE SWEET TRADITIONAL CRAFTSMEN IN THE PARISH OF CANTON ZAMORA Timbara in tourism" project is an initiative developed with the purpose of contributing to the progress of the craft and thus economic and tourism development in the said sector. Through a preliminary survey in the study area has been determined that the problematic associations of artisans Timbara parish is mainly evident in the lack of proper promotion, marketing and ignorance of the artisan process of sugar cane, which has meant that this tradition is losing strength progressively thus affecting craft associations of the parish is why for the effective implementation of this project achievable targets to harness the resource and establish development strategies and progress was raised. The overall objective of this study was to : " Strengthen partnerships artisans who make traditional sweets in the parish of the canton Timbara Zamora " , for it raised three specific objectives : to diagnose the current situation of the associations of artisans Timbara Parish Zamora canton ; propose a plan to promote and market to benefit artisans associations Parish traditional sweets and establish a training plan for associations of craftsmen of traditional sweets Timbara Zamora canton Parish. For subsequent development of the objectives was necessary to use appropriate methodologies and techniques, the first target was used methods directly, bibliographic, descriptive research, however the process was complemented with the help of techniques such as direct observation was to conduct a quick survey of the place, and the art of the interview provided important for determining the current status of data associations. The second objective of the survey technique, structured questionnaire was applied to members of the associations under study was used. Complementing the synthetic process allowed analytical method to analyze and synthesize information which identified the promotion and marketing plan for partnerships, complementing the process but is not referred to in the project was used for the design of the instruments of production ( totem ) tourist signage manual 2013 the Ministry of Tourism which allowed it to govern design parameters are used . Finally to establish the training plan that allowed the analytical method particularly study the results of the implemented surveys was used, and through descriptive method is able to raise the training plan for members of associations of artisans. Notably, the fulfillment of the objectives established results that contribute positively to the development of craft associations plasma as the current situation in which they find themselves and also proposes strategies for promoting, marketing and training to ensure good management so of the products produced as a partnership. Culminating with the project was considered among the findings that the existence of associations of craftsmen has allowed the craft of making traditional sweets in Timbara parish is kept alive until today, however it is also concluded that associations lack strategies marketing and promotion and also had little support from the local authorities, this can denote that the associations are not fully strengthened. The recommendations that arise at the end of this work are mainly directed associations artisans Timbara parish as well as the Autonomous Government Decentralized rural parish Timbara the same as is the body responsible for overseeing the existing resources in the area study and can take leadership and implementation of programs and projects described in this research paper, taking advantage of the growing political partner today with parish governments because only thus can generate more active participation and empowerment of the positioning citizens about crafts and tourism theme.